The relation between food consumption and biochemical exams and their nutritional consequences in patients treated in a Reference Hospital in Nephrology in Belém-PA (Research, Society and Development, 2022)
Introduction: Renal failure occurs when the kidneys cannot develop their regulatory functions normally, leading the patient to several disorders, such as: water retention, electrolyte dysfunction and acid-base imbalance. Objective: To evaluate the food consumption of patients undergoing Renal Replacement Therapy and compare it with biochemical tests. Methodology: This is a qualitative-quantitative, comparative, descriptive and analytical study, carried out in the Renal Replacement Therapy Sector in a referral hospital, located in Belém do Pará, between November 2021 and January 2022, where data were collected biochemicals from the patients' charts and Food Frequency Questionnaires (FFQ) were applied. Results: The study involved 43 patients. A higher consumption of carbohydrates was observed in the diet, from different sources according to the FFQ. Regarding the biochemical tests, the values ​​obtained were within the normal range. Discussion: In the present study, a prevalence in the daily food consumption of carbohydrates, fats and fried foods was observed, which may explain the changes in blood glucose levels. Regarding fruits, vegetables and animal proteins, the highest frequency was weekly. All these foods are rich in potassium and phosphorus respectively and if consumed in excess they can be harmful to the health of patients. Conclusion: Inadequate nutrition influences the alteration of biochemical tests. Elevated serum levels of macronutrients such as carbohydrate, protein and lipid, as well as micronutrients: phosphorus, potassium and sodium directly affect the quality of life of hemodialysis patients, as they attribute other symptoms to the pathology in question.